Organic fluorines as halogen bond donors: Theoretical study and crystallographic evidence. Issue 14 (20th April 2015) - Wang, Yanhua; Tong, Jianying; Wu, Weihong; Xu, Zhijian; Lu, Yunxiang
<x xml:space="preserve">Abstract</x> Organic fluorines usually cannot act as halogen bond donors, as a result of the extreme electronegativity and least polarizability of the fluorine atom. However, when the electronegative ability of the substituents bound to the carbon atom is very strong, organic fluorines do show positive electrostatic potentials (ESPs) along the CF bond and thus can form halogen bonds with electron donors. In this work, the effects of six different substituents, i.e., NO2, CF3, CN, COOH, CHO, and CCH, on the ESPs of the F atom were studied using the M06‐2x method. When two or three substituents with very strong electron‐withdrawing ability, such as NO2 and CN, are linked to the C atom, positive ESPs take place on the outermost portion of the F atom. However, the ESPs remain negative along the CF bond with the introduction of relatively weak electron‐withdrawing substituents, irrespective of the number of the subsituents. In addition, some complexes between fluorinated molecules with positive ESPs on the F atom and NH3 were calculated, to characterize the structural and energetic features of these specific halogen bonds. Finally, some crystal structures extracted from the Cambridge Structural Database were selected to provide experimental evidence of these interactions involving the CF bond. The results presented in this work are very important for the modern definition of halogen bonding as well as for the development of pharmaceuticals and a wide range of functional material. © 2015 Wiley Periodicals, Inc.